Genome-wide characterization of soybean RALF genes and their expression responses to Fusarium oxysporum - Liu, Yuhan; Chen, Yuhui; Jiang, Hengke; Shui, Zhaowei; Zhong, Yujun; Shang, Jing; Yang, Hui; Sun, Xin; Du, Junbo (Frontiers in Plant Science, 2022)
RALFs (RAPID ALKALINIZATION FACTORs) are small peptides required for plant growth, development and immunity. RALF has recently been discovered to regulate plant resistance to fungal infection. However, little is known in crops, particularly in soybean. Here, 27 RALFs were identified in the genome of Glycine max. All Glycine max RALFs (GmRALFs) and 34 Arabidopsis RALFs were classified into 12 clades via the phylogenetic analyses. Gene structures, conserved motifs, chromosome distribution and cis-elements were analyzed in this study. Furthermore, 18 GmRALFs were found in response to Fusarium oxysporum (F. oxysporum) infection in soybean and to have distinct expression patterns. Among them, secretory function of two GmRALFs were identified, and three GmRALFs were detected to interact with FERONIA in Glycine max (GmFERONIA, GmFER). Our current study systematically identified and characterized GmRALFs in the soybean genome, laying a groundwork for further functional analyses and soybean breeding.